2014
DOI: 10.1007/s10552-014-0392-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cervical lesions in Danish women before and after implementation of a national HPV vaccination program

Abstract: The incidence of cervical lesions decreased significantly in age groups with high HPV vaccine coverage, indicating an early effect of HPV vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 26 publications
2
47
1
1
Order By: Relevance
“…This cannot explain the entire increase, however, as the vast majority of samples were examined at hospital pathology departments throughout the study period. In theory, the increase could also have been due to higher screening rates, in a previous study; however, we found that a stable percentage of women were screened in 2000-2012 [28]. Lastly, an increase in the number of cases could be due to increased use of HPV testing in Denmark during the study period, as HPV testing has been found to increase the detection rates of cancer and precancerous lesions significantly, especially AIS and adenocarcinoma [49].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This cannot explain the entire increase, however, as the vast majority of samples were examined at hospital pathology departments throughout the study period. In theory, the increase could also have been due to higher screening rates, in a previous study; however, we found that a stable percentage of women were screened in 2000-2012 [28]. Lastly, an increase in the number of cases could be due to increased use of HPV testing in Denmark during the study period, as HPV testing has been found to increase the detection rates of cancer and precancerous lesions significantly, especially AIS and adenocarcinoma [49].…”
Section: Discussionmentioning
confidence: 52%
“…The coverage is lower, although allegedly the highest in the world, for 21-to 29-year-old women, with 75 % having received the first dose and 56 % all three doses by the end of 2013 [27]. Although it is still too soon to see an effect of vaccination on the incidence of cervical cancer, a statistically significant decrease in the incidence of atypia or worse and of CIN2 or worse has already been found among young women [28], and the effect on cervical precancerous lesions at population level in Denmark has been confirmed in a cohort study of individual information [29].…”
Section: Introductionmentioning
confidence: 99%
“…In Denmark, the quadrivalent HPV vaccine has been offered free of charge to 12-year-old girls since January 2009 as part of the children's vaccination program, and catch-up vaccination programs have been initiated to cover 13-to 15-yearold girls (since October 2008) and, most recently, women up to 27 years of age (from August 2012; ref. 30). …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Consistent with health benefits estimated by these models, evaluations of vaccination programs have provided a growing body of evidence that documents the initial effects of HPV vaccination on the prevalence of HPV vaccine types, genital warts, and cervical precancers in the US and around the world. [11][12][13][14][15][16][17][18] In the future, more substantial reductions in these outcomes are expected, along with reductions in cervical cancer and other HPV-associated cancers. [5][6][7][8][9][10]13,19 The first 2 HPV vaccines licensed in the US were the bivalent vaccine (2vHPV, which targets HPV types 16 and 18) and the quadrivalent vaccine (4vHPV, which targets HPV types 6, 11, 16, and 18).…”
Section: Introductionmentioning
confidence: 99%